Answer: -2a + 2b - 4
Step-by-step explanation:
Given expression
-(2a - 2) - (a - b) + (a - 6 + b)
Expand parentheses
(REMEMBER to change [+, -] signs when there is a [-] sign in front]
=-2a + 2 - a + b + a - 6 + b
Put like terms together
=-2a - a + a + b + b +2 - 6
Combine like terms
=(-2a - a + a) + (b + b) + (2 - 6)
=
![\boxed{-2a+2b-4}](https://img.qammunity.org/2022/formulas/history/college/bmp3h8sfep7gbwy6clmzlysz25783jvxa4.png)
Hope this helps!! :)
Please let me know if you have any questions